Pengenalan Kearsipan dan Pelatihan Arsip Digital untuk Pustakawan dan Tata Usaha Sekolah Se Kota Madya Pekanbaru - Rismayeti Rismayeti; Evizariza; Triono Dul Hakim; Vita Amelia (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
This service activity aims to provide understanding and training to librarians and school administrators throughout Pekanbaru City. Associated with Archive and Archive issues. The common problem of partners is that the discovery of several librarians and school administrators in Pekanbaru City Middle City does not understand the importance of managing and maintaining records properly in accordance with applicable provisions such as Law no. 43 of 2009 concerning archiving The target of the results of this community service activity is to provide increased understanding and training for Librarians and Administration on how to manage archives and implement digital archive management in libraries and in schools. activities that can be carried out in the school library and provide an understanding of the importance of maintenance (archive preservation). The output produced according to this activity plan for proposers is in the form of scientific articles and enriching teaching materials. The method of implementing activities is counseling. The delivery of material is carried out by lecturers who are members of the team that propose community service activities.